Improve Marketing Performance through Marketing Relationships and Sustainable Competitive Advantage - Hidayati, Rini; Muslikh, Muslikh (Research of Business and Management, 2023)
The objective of this study was how to increase the market performance of micro and, small, medium enterprises in Kampung Wisata Tegalwaru Bogor. We examine the effect of relationship marketing and sustainable competitiveness advantage on market performance. On the other hand, this study also examined sustainable competitive advantage as moderating variables. The survey was conducted by distributing the questionnaires to 50 micro, small, and medium enterprises (MSME). The sampling method used in this study is nonprobability sampling with a purposive technique. The results indicate that relationship marketing was influenced significantly by sustainable competitiveness advantage. Relationship marketing was influenced significantly by market performance. Sustainable competitiveness advantage was influenced significantly by market performance. Sustainable competitiveness advantage was the mediate relationship between relationship marketing to market performance. This research implies that companies can create sustainable competitive advantage for company managers as a strategic step by identifying competitors who can positively influence the implementation of management strategies that are expected to improve marketing performance to achieve sustainable competitive advantage